Party Politics in Goa: An analysis of defection cases of splits & Mergers- (1999-2002) - Balaji Sudas Shenvy (Elementary Education Online, 2023)
Splitting and merging of the political party for self growth is seen now a day in the all the states of India and this is big concern of Indian Constitution. The main objective of this research is to understand the party politics in Goa in the context of lawful defection cases leading to splits & mergers in the political parties in order to attain power. There is dearth of literature available in this arena, however, the archival newspapers available in the Goa State Central Library has plethora of factual information which has been dissected for this research in order to explore the dynamics of party politics in Goa. The major hypothesis developed for this research is that defection versus loyalty and ability versus incompetence to rule the State is one amongst the major issue which the Goa politics has faced during 1999-2002. This research work outline the political party’s merges and splits the consequences of their activity over the rule. Being in the power is the single motto of all the political party and for this they opt such unlawful activity. This research also outlines the breaking of tenth schedule of Indian Constitution in a very crucial manner and how these unlawful, activity create a negative impact on the democracy.